Electronic structure, Fermi surface and dHvA effect in YIn3, LuIn3, and YbIn3: Электронная структура и Ферми поверхность - Antonov, V.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The electronic structure, Fermi surface, angle dependence of the cyclotron masses and extremal cross sections of the Fermi surface of RIn3 (R = Y, Lu, and Yb) compounds were investigated from first principles using the fully relativistic Dirac linear muffin-tin orbital method. The effect of the spin-orbit (SO) interaction and Coulomb repulsion U in a frame of the LDA+SO+U method on the Fermi surface, orbital dependence of the cyclotron masses, and extremal cross sections of the Fermi surface are examined in details. A good agreement with experimental data of cyclotron masses and extremal cross sections of the Fermi surface was achieved.